Analisis Perubahan Medan Magnet Terhadap Energi Yang Dihasilkan Siklotron Mengunakan Program Python - Aziz, M. Ikhwan Asokhul; Za’im, Muhammad; Mukmin, Amril (Innovative: Journal Of Social Science Research, 2025)
Cancer is a disease caused by uncontrolled abnormal cell growth in the body. Cancer is included in deadly diseases. One of the treatments that are currently being developed to kill cancer cells is proton radiotherapy. Proton radiotherapy has the advantage of being able to reduce damage to healthy tissue around it. Proton radiotherapy requires an accelerator that is used to accelerate the movement of protons, one of the accelerators used for proton radiotherapy is the cyclotron. Research on cyclotrons is currently being carried out, one of which uses the incilico method using the python program. The purpose of this study is to determine the effect of magnetic fields on the energy produced by the cyclotron using the python program. The type of research used in this scientific article uses the incilico method using the python programming language written using the jupyter notebook IDE (Integrated Development Environment). The control variables in this study are proton charge, proton mass, voltage between dees, dees radius, distance between dees plates, and the speed of light. While the independent variable is the magnetic field strength and the dependent variable is the kinetic energy produced. Based on the research results, the motion of protons in a cyclotron with a proton charge of 1.602×10^(-19) C, a proton mass of 1.672×10^(-27) kg, a voltage between dees of 100,000 V, for a dees radius of 0.2 m, a distance between dees plates of 0.0005 m, and a speed of light of 3×10^8 m/s, it was found that for magnetic field strengths of 1.0 T, 1.2 T, 1.4 T, 1.6 T, 1.8 T, and 2.0 T, it produces energy of 1.644 MeV, 2.509 MeV, 3.32 MeV, 4.492 MeV, 5.89 MeV, and 7.048 MeV, respectively. The greater the magnetic field strength, the greater the number of rotations, so that it passes through the gap between dees more often, causing the proton speed to increase and produce greater energy. Based on this study, it is concluded that the greater the magnetic field strength in the cyclotron, the greater the proton energy produced so that the magnetic field strength of the cyclotron can be adjusted to the desired energy needs.